Socialization of Human Immunodeficiency Virus and Hepatitis B Surface Antigen Screening Among Second-Trimester Pregnant Women - Dian Hastari Ningrum; Asvia Rahayu; Rahmadani Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Human Immunodeficiency Virus (HIV) and Hepatitis B remain major public health concerns, particularly among pregnant women, due to the risk of mother-to-child transmission during pregnancy, childbirth, and breastfeeding. Limited knowledge among pregnant women regarding the importance of HIV and Hepatitis B Surface Antigen (HBsAg) screening may hinder early detection and the prevention of vertical transmission. This Community Service Program aimed to improve the knowledge and understanding of second-trimester pregnant women regarding the importance of HIV and HBsAg screening during pregnancy. The activity was conducted on April 18, 2026, at Grandmed Hospital, Lubuk Pakam, involving 25 second-trimester pregnant women. The program employed a one-group pre-test–post-test design through educational lectures, interactive discussions, question-and-answer sessions, and educational media. The educational materials covered the definition of HIV and Hepatitis B, modes of transmission, risk factors, the impact of infection on mothers and fetuses, and the importance of HIV and HBsAg screening as part of integrated antenatal care. The evaluation results showed that the participants' mean knowledge score increased from 58.4 in the pre-test to 87.6 in the post-test, representing an improvement of 29.2 points (49.9%). In addition, 96% of participants understood the benefits of HIV and HBsAg screening after participating in the educational program. The activity also increased participants' awareness of utilizing screening services available at healthcare facilities. Therefore, health education serves as an effective promotive strategy to support the prevention of HIV and Hepatitis B transmission while improving maternal and child health.